Comparison of GTK+ and Qt libraries in game development - Drzas, Kamil; Alchimowicz, Dominik; Pańczyk, Maciej (Journal of Computer Sciences Institute, 2018)
Game development consists of many elements. Implementation of basic features such as rendering and sound handling requires usage of low level libraries and deep knowledge. Libraries that help to create user interfaces (UI), because of their functionality, may be an attractive platform for creating basic games. This paper presents the results of comparison of the two popular libraries: GTK+ and Qt.